Homocysteine levels in women with a history of gestational diabetes mellitus. Issue 1 (December 2015) - Molęda, Piotr; Fronczyk, Aneta; Safranow, Krzysztof; Majkowska, Lilianna
Abstract Background Previous gestational diabetes (pGDM) is a risk factor of type 2 diabetes, hypertension and cardiovascular diseases. Homocysteine is one of markers of cardiovascular risk. The aim of this study was to assess the homocysteine levels in women with pGDM and to evaluate its relationship with current carbohydrate metabolism and nourishment status. Methods The study group comprised 199 women at 7.8 ± 1.0 years after pGDM and 50 control women in whom pGDM was excluded. The analyzed parameters: BMI, WHR, body composition (Tanita SC-330S analyzer), glucose and insulin levels in oral glucose tolerance test (OGTT), insulin resistance index (HOMA-IR), HbA1c, lipid profile, homocysteine, creatinine and creatinine clearance. The Mann–Whitney test and Chi–squared test were used for comparison of continuous and nominal variables, respectively. Correlations between continuous variables in each group were analyzed using Spearman's rank correlation coefficient (Rs). A logarithmic transformation was applied for variables with non-normal distribution. Results There were no differences between the pGDM women and controls in terms of age, number of childbirths, time from indexed pregnancy, pre-pregnancy BMI, or current anthropometric parameters. In pGDM women HbA1c and all glucose levels in OGTT were significantly higher, but still within the normal range. No significant differences were found in homocysteine levels, HOMA-IR, blood lipids, creatinine and creatinine clearance. Homocysteine levels did not differ significantly in subgroups categorized according to the current OGTT results or BMI. Carbohydrate metabolism disorders, overweight and obesity were associated with higher creatinine clearance. Positive correlation between homocysteine and creatinine (r = 0.21, p < 0.004), and a negative correlation with creatinine clearance (r = −0.16, p < 0.03) were found. Conclusions In women with pGDM, homocysteine is not a marker of glucose tolerance disturbances and cardiovascular risk. Increased glomerular filtration rate, observed in more severe disorders of carbohydrate metabolism and greater BMI, may temporarily protect against an increase of proatherogenic homocysteine.